Valor de la cuenta folicular antral como predictor de éxito en ciclos de fertilización in vitro. - Sánchez-Aranda, Alejandro; Alberto Campos-Cañas, Jorge; Miguel Roque-Sánchez, Armando; de Jesús López-Rioja, Miguel; Adrián Astorga-Acevedo, Ángel; Recio-López, Yesenia (Ginecología y Obstetricia de México)
BAKCGROUND: The association between ovarian reserve test and ovarian response is well established, however, its ability to predict clinical pregnancy and the live birth is limited. OBJETIVE: Evaluate the clinical usefulness of the antral follicle count (AFC) to predict clinical pregnancy and live newborn. MATERIALS AND METHODS: Retrospective cohort study was made. In fresh IVF cycles, performed at INPer between 2011-2016. Including patients diagnosed with infertility, who underwent in vitro fertilization with fresh embryo transfer. The study variables were age, antral follicle count, basal FSH concentration and number of oocytes captured. A binary logistic regression model was performed. Statistical Package for Social Sciences (SPSS) was used for the statistical analysis. The probability of error alpha <5% was considered significant. RESULTS: A total of 923 in vitro fertilization cycles were included. The antral follicle count has a prediction for clinical pregnancy (ABC 0.59) and live birth (ABC 0.57). The optimal cut-off value with the highest percentage of clinical pregnancy (9%) and live birth (10.4%) was presented with a CFA ≥ 8. A higher pregnancy rate is reported when there is a follicular count above ≥8 follicles. CONCLUSIONS: It is expected the highest number of clinical pregnancy and live birth when the antr al follicle count is for ≥8 follicles.